Magnetically treated water for irrigation: effects on production and efficiency of water use in carrot (Daucus carota L.) crop - Putti, Fernando Ferrari; Gabriel Filho, Luís Roberto Almeida; Cremasco, Camila Pires; Silva Junior, Josué Ferreira (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Carrot cultivation has increased within vegetable production because of its benefits to human health. The aim of this study was to investigate the effect of different irrigation using magnetically treated water and potable water on a carrot crop. The experiment was conducted in the Department of Rural Engineering of the Faculty of Agricultural Sciences (FCA-UNESP), Botucatu-SP Campus (Brazil), from September to December, 2015. A randomized complete block with a 2×5 factorial and 10 repetitions was adopted. Thus, the treatments included 2 types of water (potable and magnetically treated) and 5 spare blades that corresponded to the percentage of evapotranspiration (25, 50, 75, 100 and 125% ETc), with drip irrigation. The magnetically treated water irrigation yielded an increase in green root biomass, and the highest production was seen with 100 and 125% ETc, verifying the possibility of increased carrot productivity. There was a significant increase in the number of leaves, bulb length and diameter when the carrot crop was irrigated with magnetically treated water.